First-principle investigation on mechanism of Ca ion activating flotation of spodumene - Yu, Fu-Shun; Wang, Yu-Hua; Wang, Jin-Ming; Xie, Zhen-Fu; Zhang, Lei (Rare metals, 2014)
Different hypotheses of the activation mechanisms of metallic ions for silicate minerals flotation were stated in this work. Spodumene and Ca ion were taken to illustrate this issue. Flotation test results and diagram of Ca ion species distribution vs pH show that the dominant hydrolyzed species are Ca（OH）？and Ca（OH）2, which is in correspondence with the maximum flotation recovery of spodumene. Density functional theory（DFT） calculation results reveal further that the precipitation of calcium hydroxide on spodumene surface is the effective process to activate the flotation of spodumene.